MATERIAL SUBSTITUTION FOR THE SUPPORTING FRAME OF POWER TILLER WITH FINITE ELEMNT ANALYSIS APPROACH - Midian Shite; Setyo pertiwi; Wawan Hermawan; Masayuki Koike; Tomohiro Takigawa; Hideo Hasegawa (Jurnal Keteknikan Pertanian, 2006)
ABSTRACT Due to its advantageouse characteristic, aluminum is considered to substitute the existing steel as material of the supporting frame of  power tiller to meet the strength and environment concerns. The investigation was emphasized on the comparison of both material in view of stress and deformation. In this study, both experimental test and finite element (FE) analysis were employed to meet the research concem.comparison between the experimental test and numerical analysis result indicated acceptable differnces of about 7-33% wich is lower than the previouse research. Substitution with aluminum was confirmed using material index that aluminum has better performance in strength and stiffness than that of steel by prescibing minimum better performance in strength and stiffness than that of steel by prescibing minimum weight. FE analysis result revealed that aluminum model was capable of sustaining loads about equal to the steel model. It was based on its maximum von Mises stress wich was insignificatly lower than the steel model. In term of strength characteristic, strength ratio of the aluminum model was higher than the steel model. Furthemore, the substitution also resulted in redistrubuting stress into wider area and mass reduction for about 36%. Keyword: Mterial Substitution, Finite Element Methode, Static Analysis, Supporting Frame, Mass Reduction